2005
DOI: 10.1590/s0074-02762005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differentiation of Anopheles (Nyssorhynchus) benarrochi and An. (N.) oswaldoi from Southern Colombia

Abstract: Anopheles (Nyssorhynchus) benarrochi, An. (N.) oswaldoi, and An. (N.) rangeli are the most common anthropophilic mosquitoes in the southern Colombian state of Putumayo. Adult females are most commonly collected in epidemiological studies, and this stage poses significant problems for correct identification, due to overlapping inter-specific morphological characters. Although An. rangeli is easy to identify, the morphological variant of An. benarrochi found in the region and An. oswaldoi are not always easy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 22 publications
1
40
0
12
Order By: Relevance
“…Subsequently, studies have reported that these two species differ in terms of their behavioral patterns and ITS2 (Internal Transcribed Spacer) and COI molecular markers, and also possibly as malaria vectors 11,12 . Currently, A. konderi is recognized as a distinct species from A. oswaldoi s.l., although it is a member of a group of cryptic species within the A. oswaldoi complex [11][12][13] .…”
Section: The Laboratório De Genética De Populações E Evolução De Mosqmentioning
confidence: 99%
“…Subsequently, studies have reported that these two species differ in terms of their behavioral patterns and ITS2 (Internal Transcribed Spacer) and COI molecular markers, and also possibly as malaria vectors 11,12 . Currently, A. konderi is recognized as a distinct species from A. oswaldoi s.l., although it is a member of a group of cryptic species within the A. oswaldoi complex [11][12][13] .…”
Section: The Laboratório De Genética De Populações E Evolução De Mosqmentioning
confidence: 99%
“…Los especímenes capturados cuando "aterrizaban" sobre el cebo humano protegido o las hembras recién emergidas procedentes de series o isofamilias (22,23) se identificaron usando las claves morfológicas disponibles (2,5,6 (27).…”
Section: Recolección Y Taxonomía De Anophelesunclassified
“…La cercanía de A. oswaldoi con A. benarrochi B no se puede comparar en otros árboles debido a que esta última especie se reconoció recientemente (27). Su cercanía se debe a que son muy similares morfológicamente, lo que impide su separación en el estadio de adulto hembra.…”
Section: Especiesunclassified
See 2 more Smart Citations